O Brasil e a difusão internacional de programas de alimentação escolar: uma análise do caso do Benim - Borges, Mayara Drummond (2018)
This dissertation examines the process of international diffusion of the Brazilian National School Feeding Programme (PNAE) through South-South cooperation from 2011 to 2016. Through qualitative analysis, combining the case study and the process tracing techniques, the existing literature was intersected with interviews, document analysis and participant observation. The hypothesis of this research is that Brazil played a central role in the diffusion of school feeding programmes in the international scenario thought trilateral South-South cooperation with international organizations. The study was developed based on the analysis of Brazilian foreign policy, focusing on the study of cooperation, particularly the South-South and trilateral types. More specifically, the case study analyzes the South-South trilateral cooperation between the World Food Programme (WFP), Brazil and Benin. The choice of such case is justified by the fact that it is a relevant South-South cooperation programme which reflects pertinent aspects of the Brazilian modus operandi in this agenda. Throughout this work, we sought to identify and present the actions unfolding over time and the events that were determinant for the diffusion of PNAE. Although many studies focus on international cooperation, little says about the diffusion of public policies or programmes, neither about food security in the international arena. The research also aims to fill part of this gap. The Brazilian central role, in this process, could be perceived with the institutionalization of the WFP office in Brazil, the Centre of Excellence against Hunger, its sui generis characteristic and its respective actions involving the case study on Benin.